The influence of phosphorus application and varying soil pH on soil and herbage properties across a range of grassland soils with impeded drainage. (1st December 2022) - Corbett, D.; Wall, D. P.; Lynch, M. B.; Tuohy, P.
Abstract: On soils dominated by high proportions of clay and organic matter, soil acidity and poor nutrient use efficiency have a major impact on output potential. Due to the inherent chemical properties of these soils, reducing soil acidity and the prevalence of undesirable metallic cations poses challenges. As a result, these soils have a large capacity for phosphorus (P) fixation, therefore reducing plant P availability. Limestone (CaCO3 or MgCO3 ) is applied to agricultural soils to counteract soil acidity and reduce P fixation. The current study investigates the effects of four contrasting annual P application rates (0, 50, 100, 150 kg P/ha); split (50:50) between spring and summer, across soils with a range of soil pH values from a previous liming trial. The effect of soil pH ranges and P treatment rates on seasonal herbage growth and herbage P concentration was investigated over three years. Soil nutrient status was also investigated. Soil pH had a significant impact on the rate of mineralization and soil P concentration across each site. A soil pH of 6.2 caused a 1.8 mg/l increase in soil test P. An annual P application was necessary to maintain sufficient herbage P concentration for animal dietary requirements (0.35% DM), however there was no effect of P application or liming rate on herbage productivity across the three sites as all sites possessed sufficient soil P reserves. The current experiment has shown that despite optimal soil fertility status, ensuring sufficient plant available P is a problem on these particular soils.